Effects of MAL‐PDT, ingenol mebutate and diclofenac plus hyaluronate gel monitored by high‐frequency ultrasound and digital dermoscopy in actinic keratosis – a randomized trial. (6th January 2020) - Arisi, M.; Zane, C.; Polonioli, M.; Tomasi, C.; Moggio, E.; Cozzi, C.; Soglia, S.; Caravello, S.; Calzavara‐Pinton, I.; Venturini, M.; Rossi, M.T.; Calzavara‐Pinton, P.G.
Abstract: Background: The efficacy for actinic keratosis (AK) clearance of field‐directed treatments has been investigated in randomized studies against placebo, but the comparison of results is difficult for several methodological reasons. Objectives: The present study aims to compare efficacy of MAL‐photodynamic therapy (MAL‐PDT), ingenol mebutate gel (IMB) and diclofenac plus hyaluronate gel (DHA) on multiple AKs assessing a new performance index of efficacy, the cumulative AK area and evaluating dermoscopical and high‐frequency ultrasound (HFUS) changes. Methods: Patients with ≥5 Olsen II AKs in a 25 cm 2 area of the scalp and face were enrolled and randomized to one of the treatment choices. Number of AKs and cumulative area were assessed before and after treatment. Dermoscopy and HFUS were performed on a single AK and surrounding photo‐damaged skin in the treatment area. Results: Cumulative AKs area reduced significantly more with PDT compared to other treatment options and with IMB in comparison to DHA. PDT was also the only treatment option that increased at a significant level the dermal density in both target AK and the surrounding skin and decreased significantly the SLEB thickness in the perilesional skin at HFUS. Conclusions: MAL‐PDT is more effective than IMB and DHA for reducing the cumulative AK area which is calculated digitally from 3D pictures and should be the preferred performance index for the evaluation of the efficacy of treatments for AKs, rolling out clinical and dermoscopy evaluation. MAL‐PDT improves all HFUS features of chronic photodamages of the dermis of the skin underlying and surrounding the AK spots.